2004
DOI: 10.1021/cg0342314
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of a Solvent on the Crystal Habit

Abstract: The extreme polar morphology that has been observed for crystals of the stable form of a steroid is explained by a molecular dynamics simulations approach. The habit modification is caused by surface-solvent interactions, which affect the growth rate of the polar faces differently. The same effect was observed for the metastable polymorphic form. Depending on the solvent, the nature of the difference is mainly caused by the hydrogen bond interactions or the electrostatic part of the interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 8 publications
2
134
0
3
Order By: Relevance
“…Thus, it is reasonable to speculate that the observed differences in the relative intensities of the peaks in the diffractograms of the ASP-II and ASP-III crystals in comparison to the ASP-I crystal could be attributed to the crystal habit or crystal size modification (23,24). In addition, this type of diversity observed in X-ray diffractograms by various other research groups have also been related either to the interaction between the solvent and the growing crystal surface or to the presence of solvent/non-solvent in the solute lattice (25,26). The DSC thermograms of unprocessed aspirin (ASP-I) crystals, and ASP crystals generated with DEE (ASP-II) or with DCM (ASP-III) by the modified diffusion method are shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, it is reasonable to speculate that the observed differences in the relative intensities of the peaks in the diffractograms of the ASP-II and ASP-III crystals in comparison to the ASP-I crystal could be attributed to the crystal habit or crystal size modification (23,24). In addition, this type of diversity observed in X-ray diffractograms by various other research groups have also been related either to the interaction between the solvent and the growing crystal surface or to the presence of solvent/non-solvent in the solute lattice (25,26). The DSC thermograms of unprocessed aspirin (ASP-I) crystals, and ASP crystals generated with DEE (ASP-II) or with DCM (ASP-III) by the modified diffusion method are shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In the present study, it is observed that using of different non-solvents in the same crystallization process yielded different crystal habits. These differences in the crystal habit could be attributed to the non-solvent-surface-solvent interactions which lead to relative growth of the surfaces in different directions to produce a specific shape (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the solvent at the different crystalsolution interfaces may lead to altered roundness of growing crystal faces and/or edges, changes in crystal growth kinetics, and enhancement or inhibition of crystal growth at certain faces (Figure 7), thereby changing the crystal habit (Stoica et al, 2004;Tiwary, 2006). …”
Section: Solventmentioning
confidence: 99%
“…The growth interface of KDP is still beyond the reach of current methods, but for a limited number of systems involving less components, encouraging results have been obtained. 6,[39][40][41] These realistic calculations are very costly and the system size has to be quite small. Nevertheless, in this area a genuine contact between experiment and modelling is emerging.…”
Section: Closing the Gap?mentioning
confidence: 99%